In utero heat stress alters the postnatal innate immune response of pigs. (7th November 2020) - Johnson, Jay S; Maskal, Jacob M; Duttlinger, Alan W; Kpodo, Kouassi R; McConn, Betty R; Byrd, Christopher J; Richert, Brian T; Marchant-Forde, Jeremy N; Lay, Donald C; Perry, Shelbi D; Lucy, Matthew C; Safranski, Tim J
Abstract: The effects of in utero heat stress (IUHS ) range from decreased growth performance to altered behavior, but the long-term impact of IUHS on postnatal innate immune function in pigs is unknown. Therefore, the study objective was to determine the effects of early gestation IUHS on the immune, metabolic, and stress response of pigs subjected to an 8 hr lipopolysaccharide (LPS ) challenge during postnatal life. Twenty-four pregnant gilts were exposed to thermoneutral (TN ; n = 12; 17.5 ± 2.1 °C) or heat stress (HS ; n = 12; cyclic 26 to 36 °C) conditions from days 6 to 59 of gestation, and then TN conditions (20.9 ± 2.3 °C) from day 60 of gestation to farrowing. At 12 wk of age, 16 IUHS and 16 in utero thermoneutral (IUTN ) pigs were selected, balanced by sex and given an intravenous injection of LPS (2 µg/kg BW mixed with sterile saline [SAL ] and injected at 2 µL/kg BW) or SAL (2 µL/kg BW). Body temperature was monitored every 30 min, and blood was obtained at 0, 1, 2, 3, 4, 6, and 8 hr following the LPS challenge. Blood samples were analyzed for glucose, insulin, non-esterified fatty acids (NEFA ), cortisol, and cytokine concentrations. In addition, white blood cell counts were determined at 0 and 4 hr. Hour 0 data were used as covariates. Body temperature was increased ( P < 0.01) in LPS (40.88 ± 0.08 °C) vs. SAL (39.83 ± 0.08 °C) pigs. Eosinophils tended to be decreased overall ( P = 0.09; 43.9%) in IUHS vs. IUTN pigs. Glucose concentrations were reduced overall ( P = 0.05; 5.9%) in IUHS vs. IUTN pigs. The NEFA concentrations tended to be greater ( P = 0.07; 143.4%) in IUHS-LPS pigs compared with all other treatments, and IUTN-LPS pigs tended to have greater (127.4%) circulating NEFA concentrations compared with IUTN-SAL and IUHS-SAL pigs. Cortisol was increased ( P = 0.04) in IUHS-LPS compared with IUTN-LPS pigs at 3 hr (21.5%) and 4 hr (64.3%). At 1 hr, tumor necrosis factor α was increased ( P = 0.01; 115.1%) in IUHS-LPS compared with IUTN-LPS pigs. Overall, interleukin-1β (IL-1β ) and interleukin-6 (IL-6 ) were greater ( P < 0.04; 281.3% and 297.8%, respectively) in IUHS-LPS pigs compared with all other treatments, and IUTN-LPS pigs had increased IL-1β and IL-6 concentrations compared with IUTN-SAL and IUHS-SAL pigs. In summary, IUHS altered the postnatal cytokine, metabolic, and physiological stress response of pigs during postnatal life, which may have negative implications toward the innate immune response of IUHS pigs to pathogens.